Peningkatan Transparansi, Akuntabilitas, dan Partisipatif Melalui Pengelolaan Alokasi Dana Desa di Desa Tellumpanuae Kabupaten Maros - Sri Wahyuni Nur; F Fitri (Universitas Muhammadiyah Parepare)
The Village Fund Allocation which is allocated to finance the Village Government program in the implementation of the Village Fund Allocation. Also, there is the issue of accountability that is still low in the capacity of village government officials in mastering Technology, Management, and Services to the community. Problems in Participatory matters where the approved Village Fund Allocation program could not be implemented properly due to the low level of community participation. The Implementation Method consists of preparation and briefing, implementation and a sustainability plan. The results of the implementation of the KKN-PPM are the creation of regulations, accountability, and participation in the management of village allocation funds, and also the availability of information boards related to income and village assistance funds. Socialization of village grant funds and financial management seminars has been conducted to the community and village government, the results obtained from the district government to the community in terms of approval and accountability, encourage community participation in the implementation of the village fund program, and the availability of information boards for the receipt and release of village funds.